2021
DOI: 10.1021/acs.orglett.1c01703
|View full text |Cite
|
Sign up to set email alerts
|

Dual Photoredox/Cobaloxime Catalysis for Cross-Dehydrogenative α-Heteroarylation of Amines

Abstract: We report a dual-catalytic platform for the crossdehydrogenative-coupling between (benzo-)thiazoles and amines which combines low loadings of an iridium photoredox catalyst and a cobaloxime catalyst under blue light irradiation. This transformation occurs without stoichiometric oxidants, giving products in moderate to excellent yields. DFT calculations support the key role of Co(II) for rearomatization of the radical-addition intermediate to generate the product.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 21 publications
0
11
0
Order By: Relevance
“…Based on the above‐mentioned results and literature reports, [15–19] a plausible mechanistic pathway is outlined in Scheme 5. First, one electron anodic oxidation of N,N,4‐trimethylaniline 2 a would lead to the radical cation I .…”
Section: Resultsmentioning
confidence: 88%
See 1 more Smart Citation
“…Based on the above‐mentioned results and literature reports, [15–19] a plausible mechanistic pathway is outlined in Scheme 5. First, one electron anodic oxidation of N,N,4‐trimethylaniline 2 a would lead to the radical cation I .…”
Section: Resultsmentioning
confidence: 88%
“…Moreover, their scope is usually limited in terms of functional group and heterocyclic tolerance. Recently, some photocatalytic techniques have enabled remarkable methods for the direct functionalization of α‐amino C−H bonds [15,16] . In addition, several research groups have also reported electrochemical solutions [17–19] .…”
Section: Introductionmentioning
confidence: 99%
“…From the results of several control experiments and spectroscopic studies, author proposed a tentative mechanism for this transformation (Figure 12 In 2021, Teskey group reported a potential merger of the Ircatalyzed photoredox process with Co-catalyzed cross dehydrogenative α-heteroarylation of amines without stoichiometric oxidants at low catalyst loadings. [29] Under the reaction condition, α-amino radicals generated selectively at the methyl position and even this selectivity remains with cyclohexyl containing amines. Apart from acyclic amines, cyclic amines such as N-phenyl pyrrolidines undergoes this reaction to give product in good yield.…”
Section: Reactions Involving Hydrogen Evolutionmentioning
confidence: 99%
“…In 2021, Teskey group reported a potential merger of the Ir‐catalyzed photoredox process with Co‐catalyzed cross dehydrogenative α ‐heteroarylation of amines without stoichiometric oxidants at low catalyst loadings [29] . Under the reaction condition, α ‐amino radicals generated selectively at the methyl position and even this selectivity remains with cyclohexyl containing amines.…”
Section: Reactions Involving Hydrogen Evolutionmentioning
confidence: 99%
“…We started our investigation by conducting arylation of N -Me piperidine with 4-bromobenzonitrile under Ni/photoredox conditions . Gratifyingly, when reaction occurs, we observe exclusive N -Me arylation product 1 .…”
mentioning
confidence: 99%